Quick stops, volume 2 ebook - Smith, Kevin (Quick Stops (2022), 2024)
Kevin Smith and his Secret Stash Press bring you the seedy, sexy, sensational origin of the Askewniverse's sacred cow: Mooby the Golden Calf!Learn the udder truth about an American icon when a young podcaster tries to milk Mooby creator Nancy Goldruff for the bovine's beginnings, only to meat a cow tale so shocking, it turns her brain to hamburger.Collects Quick Stops Volume 2 #1–#4.